2015 International Symposium on Innovations in Intelligent SysTems and Applications (INISTA) 2015
DOI: 10.1109/inista.2015.7276727
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of consumer purchase intention between interactive and augmented reality shopping platforms through statistical analyses

Abstract: The objective of this study is to explore the effectiveness of three digital shopping platforms (Plain Interactive, Marker-based Augmented Reality and Markerless Augmented Reality), on the impressions and purchase intentions of consumers. The study is mainly interested in analysing whether intelligent shopping platforms with AR elements provide any added advantage to an advertised product in the form of favourable attitude or a stronger purchase impulse. During the tests with the three shopping platforms, quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…The researcher found that informants pre-existing brand attitudes affected their post-exposure brand attitudes. Another significant variable found in prior research are aesthetic quality, interactivity and response time which portray as the most important elements that able to solicit positive emotions and online purchasing [31]. In line with the claims, in [32] also found that the pleasure and perceived interface aesthetics are strongly related to purchase intention.…”
Section: Mmentioning
confidence: 55%
See 1 more Smart Citation
“…The researcher found that informants pre-existing brand attitudes affected their post-exposure brand attitudes. Another significant variable found in prior research are aesthetic quality, interactivity and response time which portray as the most important elements that able to solicit positive emotions and online purchasing [31]. In line with the claims, in [32] also found that the pleasure and perceived interface aesthetics are strongly related to purchase intention.…”
Section: Mmentioning
confidence: 55%
“…The exploratory study was conducted to comprehend consumer evaluation and attitude that leads to intention to purchase. On the other hands, a study of decision making by comparing two countries of youth market was conducted by [31] which quantify interactivity, response time, information quality, aesthetic quality, usefulness, enjoyment, ease of use and attitude on purchase intention. Another comparison type of study by [32] between interactive and magic mirror AR shopping platform to understand the phenomenon of attitude towards brand and purchasing intention.…”
Section: Mmentioning
confidence: 99%
“…Recently, AR experiential campaigns focus on the entire experience developed principally for the consumer. 21 And some people have applied AR for teaching. 22 However, it cannot accurately designate the target position.…”
Section: Related Workmentioning
confidence: 99%
“…gerçek ve bilgisayarla yaratılmış verilerin bir karışımı olan artırılmış gerçeklik teknolojisi, tüketiciye eğlenceli, katılımcı ve sürükleyici bir deneyim (He, Wu & Li, 2018;Stoyanova, Brito, Georgieva & Milanova, 2015) olanağı tanıdığından reklamcılar tarafından ürünleri tanıtmanın yeni bir yolu olarak kabul edilmektedir (Stoyanova vd., 2015).…”
Section: Introductionunclassified
“…Günümüzün sürükleyici dijital teknolojilerinin, tüketicinin ihtiyaç duyduğu yerde ve zamanda gerçek zamanlı, bağlama özgü uzmanlık sunarak tüketici deneyimini dönüştürme potansiyeline sahip olduğu görülmektedir (Parise, Guinan & Kafka, 2016). Özellikle, pazarlama temellerini yeniden şekillendiren, gerçek ve bilgisayarla yaratılmış verilerin bir karışımı olan artırılmış gerçeklik teknolojisi, tüketiciye eğlenceli, katılımcı ve sürükleyici bir deneyim (He, Wu & Li, 2018;Stoyanova, Brito, Georgieva & Milanova, 2015) olanağı tanıdığından reklamcılar tarafından ürünleri tanıtmanın yeni bir yolu olarak kabul edilmektedir (Stoyanova vd., 2015).…”
Section: Introductionunclassified